2015
DOI: 10.1089/hum.2014.062
|View full text |Cite
|
Sign up to set email alerts
|

Role of Transgene Regulation in Ex Vivo Lentiviral Correction of Artemis Deficiency

Abstract: Artemis is a single-stranded endonuclease, deficiency of which results in a radiation-sensitive form of severe combined immunodeficiency (SCID-A) most effectively treated by allogeneic hematopoietic stem cell (HSC) transplantation and potentially treatable by administration of genetically corrected autologous HSCs. We previously reported cytotoxicity associated with Artemis overexpression and subsequently characterized the human Artemis promoter with the intention to provide Artemis expression that is nontoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…20,21 Using this model, Multhap et al demonstrated restoration of functional T and B lymphocytes by ex vivo complementation of the Artemis deficiency in murine stem cells using a vector carrying murine Artemis cDNA driven by the human Artemis promoter. 22 Building upon these studies, we have now developed a novel lentiviral vector with the human Artemis DCLRE1C cDNA under transcriptional regulation of its own human Artemis promoter, designated AProArt. We used AProArt to transduce human ART-SCID fibroblasts and CD34…”
Section: Nkmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 Using this model, Multhap et al demonstrated restoration of functional T and B lymphocytes by ex vivo complementation of the Artemis deficiency in murine stem cells using a vector carrying murine Artemis cDNA driven by the human Artemis promoter. 22 Building upon these studies, we have now developed a novel lentiviral vector with the human Artemis DCLRE1C cDNA under transcriptional regulation of its own human Artemis promoter, designated AProArt. We used AProArt to transduce human ART-SCID fibroblasts and CD34…”
Section: Nkmentioning
confidence: 99%
“…23 Moreover, Art -/-murine HSC transduced with murine Artemis cDNA under transcriptional regulation of a strong EF1a promoter failed to engraft in Art -/-recipients. 22 To determine the optimal concentration of AProArt lentivirus for transduction of human CD34…”
Section: Determination Of Optimal Aproart Lentivirus Concentration Fomentioning
confidence: 99%
“…Several groups including ourselves have already shown that recombinant HIV-1-derived lentiviral vectors (LVs) can be used to express either murine or human Artemis proteins in hematopoietic cells to restore B and T lymphopoiesis in murine models of RS-SCID or in xeno-transplant models engrafted with transduced patient cells 8, 9, 10, 11, 12. High levels of Artemis expression appear to be toxic in vitro and in vivo 11, 13, 14. Loss of cell viability, perturbed cell cycle, increased DNA damage, and apoptosis were reported in cultured murine or human cell lines transduced with LV that strongly express either human or murine Artemis 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The in vitro effects were vector dose dependent and correlated to the strength of the promoter used in the Artemis transfer cassette. The strong elongation factor-1α (EF1a) promoter caused greater in vitro toxicity than the weaker human phosphoglycerate kinase (PGK) promoter, which is about 25% less strong in a luciferase reporter assay 11 . Artemis-deficient HSC transduced by a LV with a murine PGK promoter driving expression of murine Artemis successfully engrafted in vivo and reconstituted B and T lymphocyte compartments in Artemis-deficient mice, 8 whereas HSC transduced with a LV using stronger cytomegalovirus (CMV) or EF1a promoters failed to support lymphoid reconstitution after transplantation in RAG-1-deficient animals 10 …”
Section: Introductionmentioning
confidence: 99%
“…60 Two groups in the US have recently published their experience with a SIN lentiviral vector containing human Artemis cDNA under transcriptional regulation of the endogenous Artemis promoter. 61,62 As the moderate-strength PGK gives insufficient immune reconstitution and human EF1α-driven-Artemis overexpression can be toxic, the use of the most "endogenous" promoter may have potential to be superior. Fibroblasts from patients transduced with that lentivirus showed correction of radiosensitivity.…”
Section: Preclinical Approaches In Other Primary Immune Disordersmentioning
confidence: 99%